PEMIDANAAN TERHADAP PELAKU TINDAK PIDANA KEKERASAN DALAM RUMAH TANGGA (STUDI KASUS PUTUSAN PENGADILAN NEGERI PEKANBARU NOMOR : 192/PID.B/2009 - Nuroso '; Erdianto '; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Criminal offense of domestic violence is a criminal act that occurred in the family environment whether physical, fsikis, and sexual violence has a negative impact on domestic harmony. Pekanbaru District Court Decision No. 192 / Pid.B / 2009 / PN / PBR is one of the domestic violence case in which the defendant has been indicted by the Public Prosecutor with alternative charges, first in violation of Article 306 paragraph (2) of the Criminal Code, or both in violation of Article 44 paragraph (3) of Law No. 23 of 2004 on the Elimination of Domestic Violence. Furthermore, in reaching a decision on the case, how the judges saw as well as giving consideration to alternative charges that have been in dakwakan by the Public Prosecutor.The purpose of this thesis, namely: First, to determine punishment of perpetrators of domestic violence in the case Number: 192 / Pid.B / 2009 / PN.PBR. Second, to determine the consideration of judges in sentencing for perpetrators of violence in the home Tannga in Case Number: 192 / Pid.B / PN.Pbr. This type of research is classified in legal research is defined sociological look at the effectiveness of the law in force, with the correlation between law and society.From the results of research and discussion, it can be concluded that the First Implementation of criminal sanctions against the perpetrators of the crime of domestic violence in the case number: 192 / Pid.B / PN.Pbr. where the judges who hear the case the case after reading and understanding the relevant case files and the judges convict who has been determined by a judge that is 2 (two) Year Six Months. The perpetrator shall be punished on the basis of violation of Section 306 subsection (2) of the Criminal Code. Secondly, Considering after getting the facts and the law court to examine the chronological events Ermawati victim's death (defendant's wife) then some judges consideration in deciding Case Number: 192 / Pid.B / 2009 / PN.Pbr. namely: The judges have been doing construction by departing from the basic law used Article 306 paragraph (2) of the Criminal Code and not made Law 23 of 2004 on domestic violence as the foundation of thinking, the judges also have done silogistis coherent thought process so that all the elements are connected with the alleged facts and conclusions, that the fact that the law has met the elements of offense defined in law.Keywords: Punishment - Crime - Domestic Violence